Lipid, water, and protein composition to facilitate kinetic modeling of the auditory pathway. (2nd January 2019) - Grobe, Nadja; Narayanan, Latha; Brown, Dominique N.; Law, Sarah T.; Sibomana, Isaie; Shiyanov, Pavel; Reo, Nicholas V.; Hack, C. Eric; Sterner, Teresa R.; Mattie, David R.
Abstract: Environments combining JP-8 jet fuel exposure with heightened ambient noise may accelerate hearing loss induced by noise. To reduce animal use and facilitate kinetic modeling of this military aviation fuel, tissue-specific parameters are required, including water, protein, and lipid content. However, tissues involved in hearing, including cochlea, brainstem, frontal, and temporal lobe, have not been characterized before. Therefore, water content was determined by lyophilization of rat auditory tissues and the protein of the freeze dried remainder was quantified using a bicinchoninic acid assay. Lipids were extracted from fresh-frozen rat auditory tissues and separated into neutral lipids, free fatty acids, neutral phospholipids, and acidic phospholipids using solid phase extraction. Phospholipid fractions were confirmed by 31  P nuclear magnetic resonance analysis showing distinct phospholipid profiles. Lipid content in reference tissues, such as kidney and adipose, confirmed literature values. For the first time, lipid content in the rat auditory pathway was determined showing that total lipid content was lowest in cochlea and highest in brainstem compared with frontal and temporal lobes. Auditory tissues displayed distinct lipid fraction profiles. The information on water, protein, and lipid composition is necessary to validate algorithms used in mathematical models and predict partitioning of chemicals of future interest into these tissues. This research may reduce the use of animals to measure partition coefficients for prospective physiological models.